Weaponized social media - Gordon, Sherri Mabry (New York Enslow Publishing, 2019)
Originally conceived as a way for people to stay connected, share photographs and post information, social media has evolved. Today, it is much more than a fun communication tool, it can become a destructive weapon when exploited by the wrong people. This book explains the benefits of social media, how social media is being used as a weapon, who is weaponizing social media and why, and what readers can do to protect themselves. Includes a glossary and references.-- Publisher's website.
Then and now : a closer look at social media -- Getting off track : the impact of weaponized social media -- Online danger zone : how social media is weaponized by teens -- Information warfare : how social media is being weaponized by governments, politicians, and businesses -- Staying safe : what you need to know about weaponized social media -- Tools of the trade : how social media can become a positive weapon -- Chapter notes -- For further reading -- Glossary -- Index.-- Publisher's website.
Includes bibliographical references and index.
Keywords: Cyberbullying; Social media -- Social aspects